Pengolahan abon ikan Karandang (Channa pleurophthalmus) dengan penambahan kelapa parut. - Restu Restu (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2016)
This study aims to learn how to processing shredded fish from Karandang (Channa pleurophthalmus), in order to obtain a quality product and favored by consumers. The results showed that the addition of grated coconut as much as 10 % in the processing of shredded fish obtain the highest effectiveness index value (0.78), with the product specifications as follows : water content (10.2 %); protein content (43.1 %); fat content (17.1%); ash content (8.83 %); organoleptic value (7.8), with appearance criteria : clean and attractive (normal); aroma : typical fragrant shredded fish (normal); flavor : tasty and savory (normal). Key words : Channa pleurophthalmus, shredded fish, grated coconut.